Colon capsule versus CT colonography in patients with incomplete colonoscopy: a prospective, comparative trial. Issue 2 (24th June 2014) - Spada, Cristiano; Hassan, Cesare; Barbaro, Brunella; Iafrate, Franco; Cesaro, Paola; Petruzziello, Lucio; Minelli Grazioli, Leonardo; Senore, Carlo; Brizi, Gabriella; Costamagna, Isabella; Alvaro, Giuseppe; Iannitti, Marcella; et al.
Abstract : Objective: In case of incomplete colonoscopy, several radiologic methods have traditionally been used, but more recently, capsule endoscopy was also shown to be accurate. Aim of this study was to compare colon capsule endoscopy (CCE) and CT colonography (CTC) in a prospective cohort of patients with incomplete colonoscopy. Design: Consecutive patients with a previous incomplete colonoscopy underwent CCE and CTC followed by colonoscopy in case of positive findings on either test (polyps/mass lesions ≥6 mm). Clinical follow-up was performed in the other cases to rule out missed cancer. CTC was performed after colon capsule excretion or 10–12 h postingestion. Since the gold standard colonoscopy was performed only in positive cases, diagnostic yield and positive predictive values of CCE and CTC were used as study end-points. Results: 100 patients were enrolled. CCE and CTC were able to achieve complete colonic evaluation in 98% of cases. In a per-patient analysis for polyps ≥6 mm, CCE detected 24 patients (24.5%) and CTC 12 patients (12.2%). The relative sensitivity of CCE compared to CTC was 2.0 (95% CI 1.34 to 2.98), indicating a significant increase in sensitivity for lesions ≥6 mm. Of larger polyps (≥10 mm), these values were 5.1% for CCE and 3.1% for CTC (relative sensitivity: 1.67 (95% CI 0.69 to 4.00)). Positive predictive values for polyps ≥6 mm and ≥10 mm were 96% and 85.7%, and 83.3% and 100% for CCE and CTC, respectively. No missed cancer occurred at clinical follow-up of a mean of 20 months. Conclusions: CCE and CTC were of comparable efficacy in completing colon evaluation after incomplete colonoscopy; the overall diagnostic yield of colon capsule was superior to CTC. Trial registration number: NCT01525940.